Alternative fuel from vegetable oils and animal fats - Khalaf, Marwan Abdulmutaleb; Jassam, Omar Ibrahim; Razali, Azahari; Khalid, Amir (Penerbit UTHM, 2020)
This study investigated the properties of processing vegetable and animal fat to be used as alternative fuel. The vegetable oil processing industry comprises the abstraction and treating of oils and fats from vegetable sources. Vegetable oils and fats are principally used for human consumption but are also used in animal feed, for medicinal purposes, and certain technical applications. In contrast triglycerides, vegetable waxes lack glycerin in their structure. Although many plant parts may yield oil, in commercial practice, oil is extracted primarily from seeds, for many developing countries, the concept of employing vegetable oils as sources for diesel fuels can be attractive. Often the culture of the appropriate plant is well established, the oil extraction well developed, and handling and storage well defined. Yields per hectare of tropical crops such as palm and coconut oils far exceed the yields of vegetable oils in temperate zones. Also, the production of most tropical vegetable oils has positive energy. A rendering process is performed to remove excess fat from animal carcasses and then turned into oil. Thus, to obtain refined oil, there is process from crude palm oil that involves removal of the products of hydrolysis and oxidation or abstraction process of oil from the palm kernels. After refining, the oil may be split (fractionated) into liquid and solid phases by thermo-mechanical means such as controlled cooling, crystallization, and filtering, the later oil is competing successfully with the more expensive groundnut, corn, and sunflower oils.